Improvement of Psychiatric Symptoms by Cardiac Rehabilitation in Coronary Heart Disease - Shafti, Saeed Shoja; Ahmadie, Masuod (International Journal of Psychosocial Rehabilitation, 2018)
Introduction: The high prevalence of co-morbidly among cardiac patients may result in undesired con- sequences, which certainly can compromise their managements. Cardiac rehabilitation can be an appropriate adjunctive intervention for amelioration of such morbid processes.Method and Materials: An open comparative study had been performed between a group of ischemic cardiac patients with depressive symptoms, who received cardiac rehabilitation programs, in addition to their standard treatments (n=30), in comparison with a similar group of ischemic patients who had received only the custom- ary managements (n=30).Results: Significantly, more patients in the target group (56.6%) gained benefit from cardiac rehabilitation, in comparison with only 30 % of them in the control group (P